Food insecurity in rural Nigeria during the lean season: causes and coping strategies - Muhammad Jabo, Muhammad Sani; Ismail, Mohamed Mansor; Shamsudin, Mad. Nasir; Abdullah, Amin Mahir; Yakubu, Abdullahi Abbas (Agriculture and Environmental Science Academy, 2017)
This study used a national representative sample of 3380 household from the general household survey-panel (GHS-Panel) to examine the causes and coping strategies among the rural households in Nigeria. The post-planting survey visit, which is the first round of its kind in Nigeria was carried out in (August-October, 2010), it was done immediately after planting season to collect information on land preparation, input and labour utilization. The results shown that soaring food prices and drought together constituted the highest causes of household food insecurity with about (42%) according to the household responses. The cumulative food insecurity strategy index (CSI) is an inverse function approach, which means that an increase in the use of coping strategies indicate a decrease in food security. The results reveal that, households within the age category of greater than or equals to 71 years are having the highest CSI (71.1%). While the least food insecure are the household heads within the age cohort of 31-40 years with only 25.7 % CSI. Poverty alleviation programs and encouraging sustainable non-farm income generating activities among the rural households would have positive impact on the food security situation in rural Nigeria.